Exhaled nitric oxide measurements in patients with acute-onset interstitial lung disease. (29th June 2017) - Oishi, Keiji; Hirano, Tsunahiko; Suetake, Ryo; Ohata, Syuichiro; Yamaji, Yoshikazu; Ito, Kousuke; Edakuni, Nobutaka; Matsunaga, Kazuto
Abstract: It is important to identify the underlying cause of acute-onset interstitial lung disease (ILD). This study aims to assess whether there are differences in the exhaled nitric oxide (eNO) level between different subtypes of acute-onset ILD. Forty patients with a combination of illness ≤4 weeks in duration and diffuse radiographic infiltrates were classified into groups based on the etiology. The eNO at a flow rate of 50 ml s −1 (FeNO), the alveolar nitric oxide concentration (Calv), and the systemic inflammatory markers of the groups were compared. The median FeNO value of patients with acute eosinophilic pneumonia (AEP) (48.1 ppb) was significantly higher than that of the other groups (17.4 ppb in cryptogenic organizing pneumonia, 20.5 ppb in hypersensitivity pneumonia, and 12.0 ppb for sarcoidosis) ( p  < 0.0005) as well as blood eosinophils ( p  < 0.005) and Calv levels ( p  < 0.005). The area under the receiver's operating characteristic curve (AUC) for FeNO to identify AEP was 0.90 with a cut-off of 23.4 ppb. The AUC for Calv and blood eosinophils was 0.85 and 0.82, respectively. Even in patients with blood eosinophil numbers <5 × 10 5 cells μ l −1, FeNO maintained a good diagnostic value for AEP (AUC = 0.85). eNO can be useful for differentiating AEP from other types of acute-onset ILD, regardless of the blood eosinophil levels.